Sebaceous Carcinoma of Scalp- Rare Skin Cancer - A Case Report - Khan, Md Burhan Uddin; Kalam, Abul; Islam, Md Nazrul; Amin, Farhana; Hasan, ASM Qamrul (Journal of Surgical Sciences, 2013)
DOI: http://dx.doi.org/10.3329/jss.v16i1.14450 Journal of Surgical Sciences (2012) Vol. 16 (1) : 49-51